Decoding Everyday Signs: A Semiotic Analysis of Meaning and Culture - Rivalina, Rahmi; Anugrah, Arya; Efruan, Rachel Olivia (Paradigma Lingua, 2025)
This research explores the field of semiotics, concentrating on how signs and symbols are used to convey and interpret meaning in everyday contexts. Drawing on foundational concepts from Ferdinand de Saussure, supplemented by Roland Barthes’ cultural semiotics and Umberto Eco’s interpretative approaches, the study investigates the intricate ways in which signs operate within linguistic and cultural frameworks. Utilizing a descriptive qualitative methodology, the research gathers data from real-world environments such as streets, bus terminals, and shopping centers to identify the practical and cultural dimensions of signs. Saussure’s theory is employed to analyze the relationship between the signifier (form) and the signified (concept), revealing that signs are not merely tools for functional communication but are deeply embedded with cultural and societal significance. The findings illustrate how these signs go beyond their immediate purpose, reflecting broader societal values, norms, and contextual subtleties. By emphasizing the dual layers of functionality and cultural symbolism, the study highlights semiotics as a crucial lens for deciphering the complex messages embedded in everyday life. This underscores the power of semiotic analysis to uncover the nuanced interplay between communication, culture, and societal structures, offering deeper insights into how meaning is constructed and understood.